PENGARUH GAJI TERHADAP PRODUKTIVITAS KERJA MANDOR PANEN PERKEBUNAN KELAPA SAWIT DI KABUPATEN KUTAI KARTANEGARA THE INFLUENCE OF SALARY ON HARVESTING FOREMAN’S PRODUCTIVITY OF OIL PALM PLANTATION IN KUTAI KARTANEGARA - Nur Aini Rohmatu Jannah; Budi Winarni; Rossy Mirasari (JURNAL AGRIMENT, 2019)
To achieve high work productivity from the employees, it is important to give them a remuniration or compensation in the form of salary. This study aims to analyze the influence of compensation on harvesting foreman’s productivity. The data was collected by using questioner and by taking all the population. Meanwhile, the data were analyzed by using linear regression and determination coefficient with help of SPSS 25 program. Based on the statistical test result, salary (X) has positive influence on harvesting foreman’s productivity in oil palm plantation (Y).